Student satisfaction of university service quality in Malaysia: a review - Mohd Yusof, Norlaili; Asimiran, Soaib; Abdul Kadir, Suhaida (Human Resource Management Academic Research Society, 2022)
The attraction of new students and the retention of current students have become an imperative topic in many institutions as rivalry between institutions is growing worldwide. In order to survive, expand, and remain competitive, educational institutions must recognise the importance of service quality and student satisfaction. Therefore, providing quality education services is a high priority for all these institutions. Institutions need to truly fulfil the needs of students in order to deliver top quality services to students and recognise how cognitive factors contribute to student satisfaction. Positive expectations of service quality by current students will contribute towards positive images of the organisations, and to overall satisfaction. Thus, the purpose of this paper is to analyse the standard of university service in the satisfaction of students with a sound empirical finding. Refereed articles and conference papers were used to gather the data. The first section of the paper addresses the satisfaction of students, the quality of university service, and the second section describes the empirical results of previous research in the sense of real world. This research looked at the empirical literature on higher education with the purpose of increasing the present contribution of knowledge. The empirical findings revealed that service quality has an impact on student satisfaction in a variety of study contexts.